Dari Salaman ke Senyuman: Dampak Kebijakan Kesehatan Global terhadap Komunitas Lokal di Era Pandemi - Elsa Lutmiranita Amanatin; Naila Rahmaniyatul Wulida; Handika Mukti; Kuncoro Bayu Prasetyo; Noviani Achmad Putri; Didi Pramono (Universitas Padjadjaran, 2020)
This study describes change of people’s behavior in Debong Kidul, Tegal, in response to global policies due to Covid-19 pandemic. The Covid-19 pandemic that emerged since the beginning of 2020 has significant impact to human life around the world, including changing people’s physical interaction. This research applied qualitative methods. Data of this study were collected through direct observation, online interviews, and literature study. The finding of this study suggests that the global health policy on physical distancing was responded by the Government of Tegal by issuing local regulations to prohibit the handshaking habit during the Covid-19 pandemic. This regulation has reduced people’s habit of handshaking. However, people has adopted a new habit to substitute handsake during the social interaction by smiling.